Effect of Magnet-Fe3O4 composite structure on methane production during anaerobic sludge digestion: Establishment of direct interspecies electron transfer. (April 2022) - Li, Lei; Liu, Haoyu; Chen, Yongdong; Yang, Donghai; Cai, Chen; Yuan, Shijie; Dai, Xiaohu
Abstract: Direct interspecies electron transfer (DIET) has been shown to be more efficient than conditional mediated interspecies electron transfer via hydrogen/formate. However, the effective enrichment of functional organisms and the development of DIET to improve the anaerobic digestion performance of sludge remain a challenge. This study aimed to develop a magnet-Fe3 O4 composite structure capable of enriching functional microorganisms without the need to continuously add conductive materials. The composition of the microbial community and its corresponding functionalities were compared using metagenomic analysis in response to the addition of free Fe3 O4 and magnet-Fe3 O4 composite groups. The magnet-Fe3 O4 composite structure reduced the lag phase by 51.2% and enhanced the maximum methane production rate by 50.1% compared with those of the free Fe3 O4 group. Electrochemically active bacteria such as Dissulfurimicrobium and Geobacter were enriched in the magnet-Fe3 O4 biofilm, along with archaea Methanosaeta . The presence of DIET was proved by the enriched CO2 reduction pathway assigned to Methanosaeta and a larger quantity of type IV pili genes possessed by electrochemically active bacteria in the magnet-Fe3 O4 biofilm. These results provide a promising strategy for enriching functional microorganisms and stably improving methanogenesis efficiency in anaerobic sludge digestion systems. Graphical abstract: Image 1